Sponges on shifting reefs: holobionts show similar molecular and physiological responses to coral versus macroalgal food - Campana, Sara; Arts, Milou G. I.; Díez-Vives, Cristina; Mueller, Benjamin; Bang, Corinna; Riesgo, Ana; Haas, Andreas F.; Muyzer, Gerard; de Goeij, Jasper M. (Frontiers in Marine Science, 2024)
Introduction Many coral reefs witness an ongoing coral-to-algae phase shift. Corals and algae release large quantities of (in)organic nutrients daily, of which a large part is utilized by sponges. In turn, sponges are important cyclers of precious resources to other inhabitants on reefs residing in oligotrophic waters. Here, we investigated whether sponge holobionts (i.e., host and prokaryotic symbionts) adapt their physiology to food released by coral- versus macroalgae. Methods Thereto, two sponge species, Plakortis angulospiculatus and Halisarca caerulea (high and low microbial abundance, respectively), were continuously exposed for 12 days to coral and macroalgal exudates in running seawater aquaria. Transcript expression of host and prokaryotic symbionts, changes in prokaryotic community composition, and holobiont physiological responses (i.e., respiratory demand, fluxes of carbon and nitrogen) were investigated after coral- versus macroalgae dominated treatments and compared to a seawater only control treatment. Results In both sponge holobionts differential transcript expression between the coral and macroalgae treatments was very low (<0.01% of total transcripts). Differential expression was found in genes targeting cellular signaling pathways, e.g., cell proliferation (upregulated in coral treatment), and immune response (upregulated in macroalgal treatment). The sponge-associated prokaryotic community composition and sponge physiological responses were similar in all treatments, yet differed significantly between the two species. Discussion After 12 days of exposure sponges appear to opportunistically feed on different food sources without having to adjust their metabolic pathways or associated prokaryotic communities. This suggests that sponges could be well-adapted to predicted changes in food source availability due to coral-to-algal phase shifts on many coral reefs.